Shock index, modified shock index, age shock index score, and reverse shock index multiplied by Glasgow Coma Scale predicting clinical outcomes in traumatic brain injury: Evidence from a 10-year analysis in a single center - Lin, Po-Chen; Liu, Chi-Yuan; Tzeng, I-Shiang; Hsieh, Tsung-Han; Chang, Chun-Yu; Hou, Yueh-Tseng; Chen, Yu-Long; Chien, Da-Sen; Yiang, Giou-Teng; Wu, Meng-Yu (Frontiers in Medicine, 2022)
Abstract: Objectives: Early identification of traumatic brain injury (TBI) patients at a high risk of mortality is very important. This study aimed to compare the predictive accuracy of four scoring systems in TBI, including shock index (SI), modified shock index (MSI), age-adjusted shock index (ASI), and reverse shock index multiplied by the Glasgow Coma Scale (rSIG). Patients and methods: This is a retrospective analysis of a registry from the Taipei Tzu Chi trauma database. Totally, 1791 patients with TBI were included. We investigated the accuracy of four major shock indices for TBI mortality. In the subgroup analysis, we also analyzed the effects of age, injury mechanism, underlying diseases, TBI severity, and injury severity. Results: The predictive accuracy of rSIG was significantly higher than those of SI, MSI, and ASI in all the patients (Area under the receiver operating characteristic curve [AUROC], 0.710 vs. 0.495 vs. 0.527 vs. 0.598), especially in the moderate/severe TBI (AUROC, 0.625 vs. 0.450 vs. 0.476 vs. 0.529) and isolated head injury populations (AUROC 0.689 vs. 0.472 vs. 0.504 vs. 0.587). In the subgroup analysis, the prediction accuracy of mortality of rSIG was better in TBI with major trauma (Injury Severity Score, [ISS] ≥16), motor vehicle collisions, fall injury, and healthy and cardiovascular disease population. rSIG also had a better prediction effect, as compared to SI, MSI, and ASI, both in the non-geriatric (age <65 years) and geriatric (age ≥ 65 years). Conclusions: rSIG had a better prediction accuracy for mortality in the overall TBI population than SI, MSI, and ASI. Although rSIG have better accuracy than other indices (ROC values indicate poor to moderate accuracy), the further clinical studies are necessary to validate our results. Keywords: Traumatic brain injury, Shock index, Modified shock index, Age-adjusted shock index, reverse shock index multiplied by Glasgow Coma Scale